Anticancer activity of linalool: comparative investigation of ultrastructural changes and apoptosis in breast cancer cells. (4th July 2022) - Elbe, Hulya; Ozturk, Feral; Yigitturk, Gurkan; Baygar, Tuba; Cavusoglu, Turker
ABSTRACT: Breast cancer is the most common cancer in women ın the world. Many anticancer drugs are currently used clinically have been isolated from plant species or are based on such substances. Linalool is aromatic compounds from the monoterpene group. It is the main constituents of essential oils and show antiproliferative, antioxidant, and antiseptic properties. The aim of this study was to investigate the antiproliferativeand apoptotic, effects of linalool in MCF-7 and MDA-MB-231 human breast cancer cells. MCF-7 and MDA-MB-231 human breast cancer cells were treated with different concentrations of linalool (100, 200, 400, 600, 800, 1000 µM) at 24 h and 48 h. MTT assay for cell proliferation and Annexin V assay for apoptosis was done. The morphology of breast cancer cells was investigated by lıght mıcroscope and scanning electron microscope (SEM). The study show that linalool significantly induced apoptosis in all groups as dose and time-dependent (p < .05). Linalool has apoptotic and antiproliferative properties in a concentration and time-dependent manner in breast cancer cells. The cytotoxic effects of linalool on MCF-7 and MDA-MB-231 human breast cancer cells was found to be associated with apoptotic cell death. Linalool was more effective on MCF-7 human breast cancer cells in smaller amounts. Graphical Abstract: uf0001